(untitled) (The Research of Medical Science Review, 2025)
This study explores the relationship existing between various modes of delivery and prevalence of postpartum depression within six weeks of delivery. Important implications of postpartum depression (PPD) are the mother and infant health in a large number of women, as this condition occurs after delivery. The study is descriptive in nature and done in Khyber Teaching Hospital in Peshawar and its sample was 130. The research materials used to present the data were the Edinburgh Postnatal Depression Scale (EPDS) which is a standardized instrument and SPSS to carry out the analysis of the data. Findings denote that there is a significant difference in the rate of postpartum depression in the case of diverse modes of birth delivery, and the elective cesarean section represents the greater rate. The present study reveals a possible contribution to mode of delivery as a risk factor of PPD and the need of early screening and intervention methods